THE INDUSTRIALIZATION OF THE QUR'AN IN INDONESIA - Ahmad Saifudin (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The Qur'an as a protected holy book (al-kita>b al-mah}fu>z}) has crossed a long historical journey. It is revealed as a reading text (al-matlu>), than be a writing text (al-maktu>b). The tradtion of Qur`anic wiriting undergoes a very significant transformation; from traditional to modern (printing). Based on data, the oldest Qur`anic printing in Indonesia is found in Palembang with the codecology 21 Ramadhan 1264 H coinciding with 21 August 1848 M. This effort is done by al-Faqir ila Allah Ta'ala al-Hajj Muhammad Azhari bin Kemas al-Hajji Abdullah. The effort to print the Qur'an can not be separated from the role of the company and the government. Both have their respective roles. In general, companies play a role in producing/printing and distributing, while the government is more to the control function